POLICIES AIMED AT ENHANCING FINANCIAL INCLUSION DURING A PANDEMIC: A LITERATURE REVIEW - Serghei Petighin (Economy and Sociology)
This study examines the financial inclusion policies during pandemics, particularly focusing on their efficacy within emerging economies and areas dominated by informal sectors. The urgency and relevance of the topic are underscored by the heightened economic vulnerabilities these regions face during global health crises, such as the COVID-19 pandemic, which starkly amplify the necessity for robust financial inclusion to uphold economic resilience. The primary objectives of this paper are twofold: firstly, to critically assess the array of financial inclusion policies deployed during pandemics, and secondly, to pinpoint potential policy enhancements informed by contemporary research alongside successful international implementations.